Turtle Island : the story of North America's first people - Yellowhorn, Eldon, 1956-; Lowinger, Kathy (Annick Press, 2017)
Discover the amazing story of the Indigenous peoples of the Americas from the end of the Ice Age to the arrival of the Europeans. You'll learn what people ate, how they expressed themselves through art, and how they adapted to the land. Archaeologists have been able to piece together what life may have been like pre-contact-- and how life changed with the arrival of the Europeans.